Comparative study of business excellence frameworks and awards in Southeast Asian Countries - Sulistyo, Budi; Amani, Husni; Widaningrum, Sri; Mohammad, Musli; Ibrahim, Rasidi (2021)
Many countries have initialized and adopted the business excellence framework to encourage high-quality achievements and be recognised internationally, including in Southeast Asian Nations (ASEAN). ASEAN as an economic and political organization of 11 countries located in Southeast Asia, established a business excellence framework to promote international organizational excellence and serve as national quality awards, which most of them adopted the Baldrige Excellence Framework (BEF). This study utilizes the accumulation and analysis of qualitative information using several sources and evidence from the business excellence frameworks and awards in ASEAN countries. This paper presents analytical comparisons of various aspects of the framework, such as their goals, award and recognition, categories, and score points (scores). It also discusses the similarities and differences among them.